Hedonic Lifestyle and Self Control in NCT Merchandise Purchasing: Gaya Hidup Hedonis dan Pengendalian Diri dalam Pembelian Merchandise NCT - Nuraini Putri Prihastutik; Zaki Nur Fahmawati (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: The global growth of Korean popular culture has intensified fandom engagement and consumption-oriented activities. Specific Background: Indonesian NCT fans actively purchase idol-related merchandise, which is often linked to pleasure-oriented lifestyle tendencies and behavioral regulation. Knowledge Gap: Empirical research examining the relationship between pleasure-oriented lifestyle patterns, behavioral regulation, and merchandise buying tendencies among Indonesian NCT fans remains limited. Aims: This study analyzed the relationship between pleasure-oriented lifestyle patterns and behavioral regulation with merchandise buying tendencies among Indonesian NCT fans. Results: Using a quantitative design with accidental sampling, 384 respondents were recruited from a Twitter fanbase. Reliability testing indicated strong internal consistency across instruments. Nonparametric correlation analysis revealed significant relationships between buying tendencies and pleasure-oriented lifestyle patterns (r = 0.661; p < .001) and behavioral regulation (r = 0.586; p < .001), with behavioral regulation demonstrating a stronger statistical association. Novelty: The study provides empirical evidence linking fandom consumption patterns with lifestyle orientation and behavioral regulation using validated psychometric measures within Indonesian NCT fan communities. Implications: The findings highlight the importance of strengthening behavioral regulation and awareness of pleasure-driven lifestyle tendencies to reduce excessive merchandise purchasing and support future consumer behavior studies in fandom contexts. Highlights: Strong Association Identified Between Pleasure-Seeking Daily Patterns and Excessive Buying Tendencies. Behavioral Regulation Shows Higher Statistical Contribution Compared With Lifestyle Orientation. Online Fan Communities Demonstrate Measurable Consumption Patterns Linked to Idol-Related Products. Keywords: Hedonic Lifestyle, Self Control, Consumptive Behavior, K Pop Fandom, Nct Fans